Influence of the Environment on Body Temperature of Racing Greyhounds - McNicholl, Jane; Howarth, Gordon S.; Hazel, Susan J. (Frontiers in Veterinary Science, 2016)
Heat strain is a potential risk factor for racing greyhounds in hot climates. However, there have been limited studies into the incidence of heat strain (when excess heat causes physiological or pathological effects) in racing greyhounds. The aim of this study was to determine if heat strain occurs in racing greyhounds, and, if so, whether environmental factors (e.g. ambient temperature and relative humidity) or dog-related factors (e.g. sex, bodyweight, color) are associated with the risk of heat strain. A total of 229 greyhounds were included in over 46 race meetings and seven different race venues in South Australia, Australia. Rectal temperatures of dogs were measured pre- and post-race and urine samples collected for analysis of myoglobinuria. Ambient temperature at race times ranged between 11.0oC to 40.8oC and relative humidity ranged from 17% to 92%. There was a mean increase in greyhound rectal temperature of 2.1oC (range 1.1oC to 3.1oC). A small but significant association was present between ambient temperature and increase in rectal temperature (r2=0.033, P=0.007). The mean ambient temperature at race time, of dogs with post-race rectal temperature of or exceeding 41.5°C , was significantly greater than at race time of dogs with a post-race rectal temperature ≤41.5oC (31.2oC vs 27.3oC, respectively, P=0.004). When the ambient temperature reached 38oC, over one third (39%) of dogs had a rectal temperature >41.5oC. Over half of post-race urine samples were positive by Dipstick reading for haemoglobin/myoglobin, and of 77 urine samples positive for Dipstick readings, 95% were positive for myoglobin. However, urinary myoglobin levels were not associated with ambient temperature or post-race rectal temperatures. The mean increase in rectal temperature was greater in dark (black, blue, brindle) than light (fawn and white) coloured greyhounds. The results suggest heat strain occurs in racing greyhounds, evidenced by post-race rectal temperatures over 41.5oC and post-race myoglobinuria. Risk of heat strain may be increased in higher ambient temperatures and in darker coloured greyhounds. Further research into the incidence of heat strain in racing greyhounds, and longer term physiological responses to heat strain, are warranted.